INVESTIGATION ON PHASE COMPOSITION AND MICROSTRUCTURE OF HIGH CHROMIUM WHITE CAST IRONS ALLOYED WITH BORON (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The microstructure and phase composition of high chromium white cast iron with composition: 2.6÷3.1%C; 0.88÷1.12%Si; 0.74÷0.98% Mn; 0.85÷1.16% Mo; 11.11÷14.11% Cr, additionally doped with boron in an amount 0.002%, 0.92% and 1.34% is investigated. The microstructure of the white cast irons was studied by optical metallographic analysis, and the phase composition – by qualitative XRD analysis. An impact toughness test was conducted. The hardness HRC was tested by the Rockwell method. The microhardness HV0.1 of the metal matrix and of the carbide phase was determined. It was found that in samples containing boron, the amount of the carbide phase increases and the chromium boride phase Cr3B4 appears in them. This results in a decrease in impact toughness from 1.88 J/cm2 for the sample with 0.002% boron to 0.98 J/cm2 with 0.92% boron and 0.68 J/cm2 with 1.34% boron. The samples containing 0.92% and 1.34% boron have a higher microhardness of the metal base (824 and 766 HV0.1) compared to those with 0.002% boron (672 HV0.1).